Painless stress fractures in diabetic neuropathic feet. Issue 858 (April 1997) - Gill, G.; Benbow, S.; Tesfaye, S.; Kaczmarczyk, E.; Kaye, L.
Abstract : We describe two patients with diabetes mellitus and associated neuropathy, who presented with painless foot swelling and no history of trauma. X-Rays revealed recent underlying fractures-in one of a metatarsus, and the other of a proximal phalanx. These were assumed to be 'stress' fractures unassociated with pain because of the severe sensory neuropathy. Though spontaneous fractures in neuropathic feet have been previously described, they almost always occur in association with Charcot joints, and are usually painful. The differential diagnosis of acute swelling in the foot of a diabetic patient with sensory neuropathy should include stress fracture.